Agricultural practices as promoters of oleocanthal and oleacein availability in virgin olive oils from three olive cultivars - Miguel D. Ferro; Irene Caño-Carrillo; Bienvenida Gilbert-López; Alfonso Fernández-García; Maria João Cabrita; José M. Herrera; Maria F. Duarte (Journal of Agriculture and Food Research)
Virgin olive oil (VOO) is one of the greatest differentiating elements within the Mediterranean Diet, mainly due to its health-promoting properties associated with the presence of specific antioxidants—the phenolic compounds (PC). Among all PC in VOO, oleocanthal and oleacein are two of the most important, mainly due to their strong association with health benefits. The presence of these PC in VOO can be induced by many factors, such as agricultural management approaches. To evaluate the relevance of the agronomic practices as inducers of oleocanthal and oleacein in VOO, monovarietal VOO from three cultivars were produced —‘Cobrançosa’ (COB), ‘Arbequina’ (ARB), and ‘Galega vulgar’ (GV)—by a laboratory-scale extraction method, considering two distinct agronomic systems: organic and integrated farming systems. From the obtained VOO, oleocanthal and oleacein were quantified by HPLC-TOFMS. Significantly higher oleocanthal and oleacein concentrations were found in all organic VOO, with COB being the cultivar presenting the highest concentrations, with 561 and 268 mg/kg for oleocanthal, and 348 and 164 mg/kg for oleacein for organic and integrated VOO, respectively. In contrast, GV showed considerably lower values than COB and closer to ARB, with 110 and 0.17 mg/kg for oleocanthal, and 113 and 0.18 mg/kg for oleacein for organic and integrated farming systems, respectively. These results clearly show that both agronomic practices and cultivar can highly influence the chemical and nutritional properties of VOO, with organic farming potentiating the concentration of oleocanthal and oleacein. Of the studied cultivars, COB showed the highest concentration of the target compounds.